HUBUNGAN ANTARA AKTIVITAS FISIK DAN TINGKAT STRES DENGAN RESTING HEART RATE PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS PEMBANGUNAN NASIONAL "VETERAN" JAKARTA TAHUN 2022 - Nabilatussalma Syeftiani (2023)
Objective: Resting Heart Rate (RHR) is a simple but underutilized indicator for assessing the risk of cardiovascular disease. An increase in RHR is directly proportional to cardiovascular disease and all other causes of death and inversely related to life expectancy. Low physical activity and high levels of stress in medical students can cause an increase in RHR. This study aimed to determine the relationship between physical activity and stress levels with RHR in students of the Faculty of Medicine UPN "Veteran" Jakarta 2022. Method: This research was an observational analytic study with a cross-sectional design on 46 samples that met the criteria and were selected using a proportional stratified random sampling technique. RHR data collection was carried out by direct measurements of the respondents, while data collection on physical activity and stress levels was carried out using GPAQ and MSSQ questionnaires. Data analysis consisted of univariate analysis of each variable presented in percentage form and bivariate analysis using Chi-Square test. Result: Most of the respondents' physical activity was in the moderate category, stress levels were in the high category, and RHR was in the high category. Bivariate test results showed no significant relationship between physical activity and RHR (p = 0.665) and no significant relationship between stress and RHR (p = 0.226). Conclusion: Students are accustomed to daily physical activities and face stressors during lectures. There is a tendency for normal RHR in students with moderate to high physical activity, whereas students with severe stress tend to have high RHR.